2020
DOI: 10.1101/2020.10.01.319269
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Intrusive Experiences In Post-Traumatic Stress Disorder: Treatment Response Induces Changes In The Effective Connectivity of The Anterior Insula

Abstract: Introduction: One of the core features of posttraumatic stress disorder (PTSD) is reexperiencing the trauma. Th anterior insula (AI) was proposed to play a crucial role in these intrusive experiences. However, the dynamic function of the AI in reexperiencing trauma, as well as its putative modulation by effective therapy, still need to be specified. Methods: Thirty PTSD patients were enrolled and exposed to chemo-facilitated traumatic memory reactivation therapy. Resting-state fMRI scans were acquired before … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 82 publications
(113 reference statements)
0
5
0
Order By: Relevance
“…DMN dysfunction marked by altered withinnetwork connectivity is consistently found in schizophrenia (Krishnadas et al, 2014), major depressive disorder (Manoliu et al, in review), and dissociative identity disorder (Lebois et al, 2022). In particular, hyperconnectivity of the posterior DMN relates to re-experiencing symptoms in PTSD (Leroy et al, 2021) and dissociative symptoms in dissociative identity disorder involving perceptual and memory disturbances (Lebois et al, 2022). This matches the DMN's functions in episodic memory and visual imagery.…”
Section: Default Mode Networkmentioning
confidence: 87%
See 3 more Smart Citations
“…DMN dysfunction marked by altered withinnetwork connectivity is consistently found in schizophrenia (Krishnadas et al, 2014), major depressive disorder (Manoliu et al, in review), and dissociative identity disorder (Lebois et al, 2022). In particular, hyperconnectivity of the posterior DMN relates to re-experiencing symptoms in PTSD (Leroy et al, 2021) and dissociative symptoms in dissociative identity disorder involving perceptual and memory disturbances (Lebois et al, 2022). This matches the DMN's functions in episodic memory and visual imagery.…”
Section: Default Mode Networkmentioning
confidence: 87%
“…Across disorders, a consistent finding is insular dysfunction marked by reduced connectivity within the SN. This is evident in schizophrenia during acute psychosis and remission (Manoliu et al, 2013b), major depressive disorder (Manoliu et al, in review), and post-traumatic stress disorder (PTSD) (Leroy et al, 2021). Aberrant SN connectivity also correlates dimensionally with symptom severity, linking to positive symptoms in schizophrenia (Krishnadas et al, 2014) and depressive symptoms in major depressive disorder (Manoliu et al, in review).…”
Section: Salience Networkmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies have shown that activity in posterior insula also enhances in response to intense experiences of social pain and exclusion, such as romantic rejection ( 43 , 44 ). Posterior insula has also been implicated in intrusive or “re-experiencing” symptoms of post-traumatic stress disorders (PTSD) (e.g., flashbacks, nightmares, recurrent and unwanted distressing memories) ( 45 , 46 ). Exposure to PV during adolescence is also an intense and traumatic experience for many youth which impacts their self-esteem and threatens their feelings of social connection ( 47 , 48 ).…”
Section: Discussionmentioning
confidence: 99%